Nursing Students' Views on Distance Education and Anxiety Levels in Covid-19 Process - Hanife Durgun; Tayfur Can; Ayşe Betül Avcı; Betül Kalyoncuoğlu (Dokuz Eylul University, 2021)
Background: In the Covid -19 pandemic during, distance education methods have been widely used in order to ensure the continuity of education at all educational levels. Objectives: The aim of this study was to investigate the relationship between nursing students' views on distance education and anxiety levels during the Covid-19 pandemic process. Methods: This descriptive and correlational type study was conducted between May and June 2020. The population of the research consisted of 80.000 students who are studying in the nursing department in Turkey. The sample was composed of 810 nursing students who were known formula. As a data collection tool; Personal Information Form, Perception Scale for Distance Education, State-Trait Anxiety Inventory were used. The data obtained; were analyzed using number, percentage, mean and t test, Mann Whitney U test, Kruskal Wallis Test and Oneway Anova. Results: The mean score of the students' Perception Scale for Distance Education, was 46.35 ± 9.13, the mean score of State Anxiety Inventory was 47.66 ± 11.91 and the mean score of Trait Anxiety Inventory was 46.39 ± 8.42. There was a statistically significant negative correlation between Perception Scale for Distance Education and State Anxiety Inventory scores (r = -.22, p = .001), there was not a statistically significant between Perception Scale for Distance Education and Trait Anxiety Inventory scores (r = -.02, p = .524). There was a statistically significant was found between the Perception Scale for Distance Education and class status, between the State and Trait Anxiety Inventory and income levels.Conclusion: It is observed that the students' perception scale for distance education and status and trait anxiety levels are moderate. The anxiety levels decrease as the students have a positive view towards distance education. In line with these results, it may be suggested to consider the solution suggestions suggested by the authoritarians and to complete the practical parts of the applied courses with remedial training in order to maintain the positive attitudes of students towards distance education and to keep their anxiety levels at a low level.